Exploration of Islamic Values In Arisan - Rokhim, Abdul (International Journal of Psychosocial Rehabilitation, 2020)
In the constellation of social activities, arisan functions as a medium to visit each other, get to know each other, strengthen ties of friendship, give and need each other, and as a medium of harmony. Meanwhile, as an economic activity, arisan has a savings and loan function. Each member of an arisan colleague has two roles, namely as a creditor as well as a debtor. Furthermore, arisan is also used as an alternative economic solution to addressing the practice of usury. So far, the practice of banking, especially conventional ones, uses the interest system. Therefore, institutional factors play a significant and dominant role in determining people's attitudes today towards interest. The practice of gathering into activities that have a tradition in goodness. Therefore, this paper intends to explore the Islamic values contained in the arisan activities conducted by most people in Indonesia. Because in the early days of Islamic, arisan was never done. Thus, the exploration of Islamic values aims to find out the economic values of Islam contained in the practice of arisan in the community.